2020
DOI: 10.1016/j.cegh.2019.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, pattern, and associated psychosocial factors of headache among undergraduate students of health profession

Abstract: Background: Headache is a common health problem among health professional students which may negatively affect their academic performance and quality of life. The study aimed to determine the prevalence, pattern, associated psychosocial factors and treatment seeking behavior regarding headache among the students of health profession. Methods: The cross sectional study was undertaken during April-September 2016 involving 339 students studying medical, dental and nursing health sciences in KIIT University, Bhuba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 32 publications
5
27
0
1
Order By: Relevance
“…Only 23.7% of study participants reportedly sought medical advice. These results were in line with other previous studies published around the world [ 14 , 33 , 34 , 35 ]. For instance, Alkarrash et al found that, among undergraduate students at the University of Aleppo, 15.9% sought medical attention [ 35 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Only 23.7% of study participants reportedly sought medical advice. These results were in line with other previous studies published around the world [ 14 , 33 , 34 , 35 ]. For instance, Alkarrash et al found that, among undergraduate students at the University of Aleppo, 15.9% sought medical attention [ 35 ].…”
Section: Discussionsupporting
confidence: 94%
“…Based on the frequency of headaches, our study revealed that 66.1% reported headaches weekly, 24.2% complained of headaches five days a week, and 42.8% had four episodes of headaches in a day. A study on undergraduate students of health professions showed that 43.5% of respondents complained of headaches monthly, 37.5% had this complaint on weekly basis, and 19% experienced it daily [ 33 ]. Recently, a study in Bangladesh conducted on university students reported that more than two-thirds of the students had more than five attacks during the past month [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…This condition minimizes the occurrence of worries because of the increased ability to recognize risks and preventive behavior so that they can anticipate more readily. Including the impact of psychosocial burden due to the quarantine process 12,22,23 . In general, education was reported in several studies as a positive determinant of program performance in health [24][25][26] .…”
Section: Resultsmentioning
confidence: 99%
“…[25] A similar situation is observed in the professional life, students studying at the health faculty have problems with falling asleep and are not healthy. [26][27][28] Therefore, it is thought that this result may be related to risk factors.…”
Section: Discussionmentioning
confidence: 99%